The Production and Sintering of Powdered Cobalt - Honeycombe R. W K; Greenwood J. N (The Australasian Institute of Mining and Metallurgy, 1942)
Powder metallurgy has been developed rapidly in the last twenty years by overseas metallurgists. The technique of making the powders and their subsequent pressing and sintering into useful forms has' only been introduced into Australia under the stress of war-time economic conditions.The technique involved has very little in common with our usual methods of fabricating engineering alloys by melting the ingredients to a homogeneous mass, followed by casting to shape or casting to ingot form and shaping by application of pressure-so-called mechanical working. On the other hand, the technique includes operations, such as milling and sizing, familiar to the primary metallurgists.The compacting of metal or other powders finds important application in two outstanding fields of engineering production: (a) in making porous bearings and contact brushes, in which such a material as powdered graphite can be incorporated; (b) in making cutting tool tips of hard -carbides, which have a melting point too high to make casting feasible, and which would be too brittle in the cast condition in any case. In both these cases; the final article can be made of the desired shape and size (subject to shrinkage allowances) whilst the compact is in a soft and readily machined condition a consideration of great importance in connection with the hard carbides.In order to develop the necessary equipment and technique and at the same time to assisil in the war effort, it was decided to divert the research work of the Metallurgy Department of the University of Melbourne to the problems associated with the production of hard carbides from local raw materials and the sintering of such into tips for cutting tools. Since this work was started at least two industrial concerns have started to produce these materials in the Commonwealth.The work. to date has included (a) the purification of crude cobalt oxide from Risdon and the reduction of this to metal Particles of less than 10 p. diameter; (b) the production of tungsten powder from King Island scheelite and its conversion into tungsten carbide with particle size less than 4 p. diameter; (c) the sintering of the latter product, using the former as a bond; (d) the production of titanium carbide from titanium dioxide; (e) the separation of columbium and tantalum oxides from a Northern Territory tantalite, and the conversion of these into the respective carbides.